The Structural Model: a theory linking connections, plasticity, pathology, development and evolution of the cerebral cortex - García-Cabezas, Miguel Ángel; Zikopoulos, Basilis; Barbas, Helen (Brain Structure and Function, 2019)
The classical theory of cortical systematic variation has been independently described in reptiles, monotremes, marsupials and placental mammals, including primates, suggesting a common bauplan in the evolution of the cortex. The Structural Model is based on the systematic variation of the cortex and is a platform for advancing testable hypotheses about cortical organization and function across species, including humans. The Structural Model captures the overall laminar structure of areas by dividing the cortical architectonic continuum into discrete categories (cortical types), which can be used to test hypotheses about cortical organization. By type, the phylogenetically ancient limbic cortices—which form a ring at the base of the cerebral hemisphere—are agranular if they lack layer IV, or dysgranular if they have an incipient granular layer IV. Beyond the dysgranular areas, eulaminate type cortices have six layers. The number and laminar elaboration of eulaminate areas differ depending on species or cortical system within a species. The construct of cortical type retains the topology of the systematic variation of the cortex and forms the basis for a predictive Structural Model, which has successfully linked cortical variation to the laminar pattern and strength of cortical connections, the continuum of plasticity and stability of areas, the regularities in the distribution of classical and novel markers, and the preferential vulnerability of limbic areas to neurodegenerative and psychiatric diseases. The origin of cortical types has been recently traced to cortical development, and helps explain the variability of diseases with an onset in ontogeny.